Surpassing the single-atom catalytic activity limit through paired Pt-O-Pt ensemble built from isolated Pt1 atoms - Hui Wang (Nature Portfolio, 2019)
Single-atom metal catalysts offer maximized material efficiency, but there is large room to improve the intrinsic activity per metal atom for many reactions. Here, the authors demonstrate that the solution for CO oxidation is to tackle the issue of lacking neighboring Pt atoms in the single-atom Pt1/CeO2 system.